bahasa inggris - Yaramah, Wati; Fitri Dianingsih, Ayu (International Journal of Digital Entrepreneurship and Business, 2024)
This study aims to examine the effects of Audit Committee Tenure, Audit Committee Meeting, Institutional Ownership, and Company Age on Earnings Management in industrial sector companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2023 period. The research employed a quantitative approach using multiple linear regression analysis with EViews 12 software. Data were collected from 20 industrial companies selected through purposive sampling, and the dependent variable, earnings management, was measured using the Modified Jones Model as a proxy for discretionary accruals. The results indicate that Company Age has a negative and significant effect on earnings management, while Audit Committee Tenure, Audit Committee Meeting, and Institutional Ownership have no significant impact. These findings suggest that older companies tend to have lower tendencies to engage in earnings management practices. The implications highlight the importance of corporate governance effectiveness and the role of company maturity in shaping the integrity of financial reporting. For regulators, auditors, and management, the study provides insights to enhance oversight mechanisms, strengthen financial transparency, and promote ethical governance practices. Keywords: Earnings Management, Audit Committee Tenure, Audit Committee Meeting, Institutional Ownership, Company Age.